A 5-HT Antagonist (UP 26-91) versus Codeine and Placebo in a Human Experimental Pain Study. (1st June 2000) - Arendt-Nielsen, Lars; Pedersen, Poul; Poulsen, Lars; Andersen, Ole Kæseler; Bjerring, Peter; Coste, Isabelle; Insuasty, Jorge; Sindrup, Søren; Drewes, Asbjørn Mohr
Abstract : BACKGROUND: This double-blind, randomized, crossover study compared the potential analgesic effect of the serotonin receptor antagonist UP 26-91 (50 mg, 150 mg and 300 mg) with that of codeine (100 mg) and placebo by use of different human experimental pain models. SUBJECTS AND METHODS: In experiment 1, pain detection and tolerance thresholds to heat, pressure and pain ratings during the cold pressor test were measured. In experiment 2, the pain threshold to single and repetitive (temporal summation) electrical sural nerve stimulation, and the pain intensity on a visual analogue scale to supra pain threshold electrical stimulation (stimulus-response-function) were measured. Tests were performed before, and 1, 2 and 6 h after drug administration. RESULTS: UP 26-91 did not show a marked effect on the experimental pain tests. Most of the variables tended to show a better effect from codeine than from placebo, but statistical significance for peak pain was only reached during the cold pressor test (P=0.011). CONCLUSIONS: In the present doses, the serotonin antagonist UP 26-91 had no effect on the experimental pain models applied.